Morphological and genetic differentiation of heteromorphy in Labidocera rotunda (Copepoda, Calanoida, Pontellidae) - Jeong, Hyeon Gyeong; Soh, Ho Young; Suh, Hae-Lip (Zootaxa, 2014)
The pontellid calanoid Labidocera rotunda Mori, 1929 is relatively widespread in the inshore surface waters of East Asia. In this study, some heteromorphic specimens have been observed with extreme morphological discrepancies in the female, including the genital double-somite, the second urosomite, the caudal rami, and the fifth leg. To evaluate the validity of species assignment of the morphological variants, we analyzed the DNA sequences of two mitochondrial genes, 16S rRNA and cytochrome oxidase subunit I (mtCOI). The specimens were collected in the Yellow Sea, the East China Sea and the East Sea (Sea of Japan) around Korea. They differed by <2.9% for mt16S rRNA and by 3.7%–4.7% for mtCOI, suggesting that they are conspecific despite their considerable morphological differences. In contrast, Labidocera japonica Mori, 1935, a morphologically similar species to L. rotunda, displayed interspecific variation of 6.1%–7.2% for mt16S rRNA and 15.1%–16.7% for mtCOI.